Studies of Physical Parameters of Indigenous Artifacts: Collecting and Preserving the Relating Oral Stories - Sardarli, Arzu; Siegfried, Evelyn; Swan, Ida; Panas, Tim; Volodin, Andrei; Kingfisher, Leta; Patterson, William; Timsic, Sandra (Engaged Scholar Journal)

(untitled) (University of Saskatchewan, 2022)
This project, supported by the Department of Canadian Heritage, was conducted by scholars from the First Nations University of Canada, Royal Saskatchewan Museum, University of Regina, and University of Saskatchewan in collaboration with Sturgeon Lake and Pelican Narrows First Nations communities in Canada. The objectives of the project were (i) to develop a research ethics protocol for collecting, studying, and preserving Indigenous artifacts; (ii) to determine physical parameters of artifacts from communities and Royal Saskatchewan Museum collections; and (iii) to collect oral stories in communities. Within the project, we also managed consultations with Elders and Indigenous Knowledge Keepers, organized two workshops in the communities, and trained Indigenous students for working in the communities. The laboratory measurements were carried out at the Scanning Electron Microscope Laboratory of the University of Alberta, Saskatchewan Isotope Laboratory of the University of Saskatchewan, and André E. Lalonde Accelerator Mass Spectrometry Laboratory of the University of Ottawa. We analyzed the data obtained from the measurements of physical parameters of artifacts collected in these communities and selected from the Royal Saskatchewan Museum collections. The purpose of the statistical analysis was to determine the similarities of artifacts with respect to their chemical compositions.